Radiologist’s clinical information review workstation interfaced with digital dictation system - McEnery, Kevin W. (Springer-Verlag, 2000)
Efficient access to information systems integrated into the radiologist’s interpretation workflow will result in a more informed radiologist, with an enhanced capability to render an accurate interpretation. We describe our implementation of radStation, a radiologist’s clinical information review workstation that combines a digital dictation station with a clinical information display. radStation uses client software distributed to the radiologist’s workstation and central server software, both running Windows NT (Microsoft, Redmond, WA). The client sytem has integrated digital dictation software. The bar-code microphone (Boomerang, Dictaphone Corp, Stratford, CT) also serves as a computer input device forwarding the procedure’s accession number to the server software. This initiates multiple quaries to available lagacy databases, including the radiology information system (RIS), laboratory information system, clinic notes, hospital discharge, and operative report system. The three-tier architecture then returns the clinical results to the radStation client for display. At the conclusion of the dictation, the digital voice file is transferred to the dictation server and the client notifies the RIS to update the examination status. The system is efficient in its information retrieval, with queries displayed in about 1 second. The radStation client requires less than 5 minutes of radiologist training in its operation, given that its control interface integrates with the well-learned dictation process. The telephone-based dictation system, which this new system replaced, remains available as a back-up system in the event of an unexpected digital dictation system failure. This system is well accepted and valued by the radiologists. The system interface is quickly mastered. The system does not interrupt dictation workflow with the display of all information initiated with examination bar-coding. This system’s features could become an accepted model as a standard tool for radiologists.